2018
DOI: 10.3389/fphar.2018.01373
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the Vitamin D Receptor Regulated Gene Set in the Hippocampus After MDMA Treatment

Abstract: The active ingredient of ecstasy, ±3,4-methylenedioxymethamphetamine (MDMA), in addition to its initial reinforcing effects, induces selective and non-selective brain damage. Evidences suggest that the hippocampus (HC), a central region for cognition, may be especially vulnerable to impairments on the long-run, nevertheless, transcription factors that may precede and regulate such chronic changes remained uninvestigated in this region. In the current study, we used gene-set enrichment analysis (GSEA) to reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Furthermore, Vit D is capable of maintaining the oxidant-antioxidant equilibrium through increasing intracellular antioxidants concentration and eliminating excess free radicals, and thereby down-regulating the oxidative stress (23,24). In addition, it has been reported that Vit D stimulates gamma-glutamyl transpeptidase (GGT) activity preventing hippocampal damage (25,26). It is worth mentioning that Vit D receptors are widely expressed in different regions of the brain, like the hippocampus (27).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Vit D is capable of maintaining the oxidant-antioxidant equilibrium through increasing intracellular antioxidants concentration and eliminating excess free radicals, and thereby down-regulating the oxidative stress (23,24). In addition, it has been reported that Vit D stimulates gamma-glutamyl transpeptidase (GGT) activity preventing hippocampal damage (25,26). It is worth mentioning that Vit D receptors are widely expressed in different regions of the brain, like the hippocampus (27).…”
Section: Introductionmentioning
confidence: 99%